Homogenous and Microbeam X-Ray Radiation Induces Proteomic Changes in the Brains of Irradiated Rats and in the Brains of Nonirradiated Cage Mate Rats - Richard Smith; Jiaxi Wang; Colin Seymour; Cristian Fernandez-Palomo; Jennifer Fazzari; Elisabeth Schültke; Elke Bräuer-Krisch; Jean Laissue; Christian Schroll; Carmel Mothersill (SAGE Publishing, 2018)
To evaluate microbeam radiation therapy (MRT), for brain tumor treatment, the bystander effect in nonirradiated companion animals was investigated. Adult rats were irradiated with 35 or 350 Gy at the European Synchrotron Research Facility using homogenous irradiation (HR) or MRT to the right brain hemisphere. The irradiated rats were housed with nonirradiated rats. After 48 hours, all rats were euthanized and the frontal lobe proteome was analyzed using 2-dimensional electrophoresis and mass spectrometry. Proteome changes were determined by analysis of variance ( P < .05). Homogenous irradiation increased serum albumin, heat shock protein 71 (HSP-71), triosephosphate isomerase (TPI), fructose bisphosphate aldolase (FBA), and prohibitin and decreased dihydrolipoyl dehydrogenase (DLD) and pyruvate kinase. Microbeam radiation therapy increased HSP-71, FBA, and prohibitin, and decreased aconitase, dihydropyrimidinase, TPI, tubulin DLD, and pyruvate kinase. Cage mates with HR irradiated rats showed increased HSP-71 and FBA and decreased pyruvate kinase, DLD, and aconitase. Cage mates with MRT irradiated rats showed increased HSP-71, prohibitin, and FBA and decreased aconitase and DLD. Homogenous irradiation proteome changes indicated tumorigenesis, while MRT proteome changes indicated an oxidative stress response. The bystander effect of proteome changes appeared antitumorigenic and inducing radioresistance. This investigation also supports the need for research into prohibitin interaction with HSP-70/71 chaperones and cancer therapy.